Foreign exchange rate regimes and fiscal discipline in the Caribbean - Seerattan, Dave ([Caribbean Centre for Money & Finance] [St. Augustine]TT, 1999)
Explores whether the conventional wisdom that fixed rate regimes generates more fical displine holds true in the region, by confronting a relatively simple model of fiscal adjustment with data from select Caribbean countries.